2018
DOI: 10.1108/jsit-04-2017-0025
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of fitness wearables

Abstract: Purpose This paper aims to analyse the adoption of fitness wearables by using the unified theory of acceptance and use of technology (UTAUT). The study analyses the relative weights and causal combinations of antecedent variables on use and intention to use fitness wearables. Design/methodology/approach The study design involves two stages: first, from the perspective of variable-oriented analysis, a structural equation model is tested using partial least squares (PLS) technique on a sample of 176 adopters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 42 publications
4
36
0
Order By: Relevance
“…This finding is consistent with previous studies that have provided empirical evidence confirming the significant, positive effect of EE on UB (Wu and Tao, 2007). Previous literature confirms that EE is an important factor in the adoption of IT in different countries (Abdul-Rahman et al, 2011;AlAwadhi and Morris, 2008;Weerakkody, 2009, 2010;Al-Sobhi et al, 2011;Foon and Fah, 2011;Reyes-Mercado, 2018;Venkatesh et al, 2003Venkatesh et al, , 2011. Importantly, there is a "need for skilled human resources for e-government success" [Khan et al, (2012), p.451].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with previous studies that have provided empirical evidence confirming the significant, positive effect of EE on UB (Wu and Tao, 2007). Previous literature confirms that EE is an important factor in the adoption of IT in different countries (Abdul-Rahman et al, 2011;AlAwadhi and Morris, 2008;Weerakkody, 2009, 2010;Al-Sobhi et al, 2011;Foon and Fah, 2011;Reyes-Mercado, 2018;Venkatesh et al, 2003Venkatesh et al, , 2011. Importantly, there is a "need for skilled human resources for e-government success" [Khan et al, (2012), p.451].…”
Section: Discussionsupporting
confidence: 92%
“…They have also tested 32 of the constructs taken from eight of the theoretical models in order to identify the most influential construct to explain the use of IT (Venkatesh et al, 2003). It was also confirmed by UTAUT theory and other recent studies (Alshehri et al, 2012;Reyes-Mercado, 2018) that the intention to use IT system is a major direct determinant of system use (Wu and Tao, 2007).…”
Section: Ub and Cuimentioning
confidence: 66%
“…The easier the individuals believe the fitness apps are to use, the higher is their intention to use them. Prior studies have revealed a positive relationship between effort expectancy and behavioral intention to use fitness apps [15,19] and fitness wearables [18,34]. As people should be interested in intuitive and easy app usage, we expect the following: Hypothesis 2: effort expectancy is positively related to behavioral intentions of individuals to use fitness apps.…”
Section: Effort Expectancymentioning
confidence: 96%
“…Performance expectancy is defined as the "degree to which using a technology will provide benefits to consumers in performing certain activities" [9]. It was the strongest predictor of behavioral intentions in the original UTAUT study [8] and is a pivotal determinant of new technology acceptance in health care [32,33] and fitness wearables [21,34]. In the context of this study, performance expectancy refers to the degree to which a user believes that using a particular fitness app would help improve their fitness.…”
Section: Performance Expectancymentioning
confidence: 97%
“…Considering that there are errors in the measurement process of tuning fork frequency, which makes the measurement result nonrandom deviation, the partial least square model is selected for fitting [27]. e Figure 13 describes the frequency-density curve and its standard residual based on the least square model fitting.…”
Section: Data Processing and Analysismentioning
confidence: 99%